Sobre la naturaleza jurídica de los modelos de prevención de delitos como eximente de la responsabilidad penal de la persona jurídica - Gómez Martín, Víctor (Pontificia Universidad Católica del Perú, 2025)
Circular 1/2016 of the State Attorney General’s Office of Spain points out that the question relating to the legal nature of the crime prevention models referred to by the CP after the 2015 reform depends on the solution adopted before the no less controversial question of the nature of the model for attributing criminal liability to the legal entity. Without prejudice to other suggestive approaches, the positions held on the matter that has just been raised are divided, in essence, into two large groups: those according to which the reference exemption from criminal liability would be due to the exclusion of the categories of atypicality or guilt, on the one hand; and those that consider, on the other hand, that the compliance defense would be linked, instead, to punishability. In the following lines, these positions will be presented and critically evaluated, as well as the conceptual budgets from which they start, to later develop my own personal positioning.

Apunta la Circular 1/2016 de Fiscalía General del Estado de España que la cuestión relativa a la naturaleza jurídica de los modelos de prevención de delitos referidos por el CP tras la reforma de 2015 depende de la solución que se adopte ante la no menos controvertida cuestión de la naturaleza del modelo de atribución de responsabilidad penal a la persona jurídica. Sin perjuicio de otros sugerentes abordajes, las posturas sostenidas sobre el particular que acaba de ser planteado se dividen, en esencia, en dos grandes grupos: aquellas según las cuales la exención de responsabilidad penal de referencia obedecería a la exclusión de las categorías de la tipicidad o de la culpabilidad, por un lado; y las que consideran, por otra parte, que la eximente de compliance se encontraría vinculada, en cambio, a la punibilidad. En las siguientes líneas se expondrán y valorarán críticamente dichos posicionamientos, así como los presupuestos conceptuales de los que parten, para desarrollar posteriormente mi propio posicionamiento personal.
On the legal nature of crime prevention models as exemption from criminal liability of legal entities
Keywords: Criminal liability of legal entities; Crime prevention models; Criminal compliance; Excuse; Responsabilidad penal de las personas jurídicas; Modelos de prevención de delitos; Compliance penal; Eximente; https://purl.org/pe-repo/ocde/ford#5.05.00